Monitoring the Compliance of Balancing Reserves Power with the System Operation ⋆ Guideline of Continental Europe. Issue 9 (2022) - Maucher, Philipp; Lens, Hendrik
Abstract: This paper describes an automatic monitoring concept for automatic and manual Frequency Restoration Reserves during operation. There is increasing need for such automatic monitoring due to the increasing share of small decentralized technical units in balancing reserves power provision. For this purpose, an existing procedure for monitoring Frequency Containment Reserves is adapted to automatic and manual Frequency Restoration Reserves. Apart from the requirements for the activation dynamics, these differ from Frequency Containment Reserves by the fact that positive and negative provision may be different. These aspects are taken into account. In order to monitor different balancing reserves power products, the measured active power that is provided to the grid has to be apportioned among the different products. In any case, the power related to the nominal schedule and the balancing reserves power have to be separated. In addition, several kinds of balancing reserves may be provided simultaneously, so that these have to be split as well. This paper proposes to perform the separation of different kinds of balancing reserves based on dynamic models that reflect the provision as good as possible. For the utility, providing this model may be difficult and conflicts of interest may arise. Therefore, we propose to identify the necessary models from measurement data. The paper shows that this procedure can be applied successfully on real measurement data.